Adaptation of different generations of hereford and aberdeen angus breeds to the ambient temperature of the Northern region of Kazakhstan - Zhigerbaevich, Kazhgaliyev Nurlybay; Dorjbat, Yol; Eginbayevich, Titanov Zhanat; Bolatbek, Ateikhan (Proceedings of the Mongolian Academy of Sciences, 2023)
This article presents the findings of a study examining how Hereford and Aberdeen-Angus breeds are adapting to ambient temperatures in northern Kazakhstan. The study suggests that animals of second and third generations display the highest levels of adaptability to high temperatures in their environment, thus requiring less stress on their protective bodily functions. These groups also exhibit a more sophisticated system of thermoregulation, enabling them to efficiently allocate body resources in hot weather, a common occurrence during the summer months in the northern region of Kazakhstan. These findings contribute to a deeper understanding of the mechanisms involved in breed adaptation to environmental conditions and the findings could be valuable to farmers and breeders in the region seeking to optimize their animal production practices.